Functional Ingredients from Fishery By-products: Nutraceutical and Pharmaceutical Applications - Pandiyan, Praveenkumar; Alamelu, Venkat; Vimaladevi, Sekar; Nicy, Brita (International Journal of Bio-resource and Stress Management, 2025)
The sustainable utilization of fishery by-products has gained significant attention for their potential bioactive compounds with nutraceutical and pharmaceutical applications. Fish heads, skins, bones, and viscera, once considered waste, were now recognized for their rich content of proteins, peptides, omega-3 fatty acids, collagen, chitin, and various antioxidants. These compounds exhibited bioactivities such as anti-inflammatory, antioxidant, antimicrobial, and antihypertensive effects, making them valuable for health-promoting applications. Proteins and bioactive peptides derived from fishery by-products contributed to cardiovascular health, immune modulation, and metabolic regulation. Omega-3 fatty acids, mainly found in fish oils, support brain function, cardiovascular health, and inflammatory disease management. Chitin and chitosan from crustacean shells exhibited wound-healing, antimicrobial, and drug delivery properties. Marine collagen and gelatin, obtained from fish skins and bones, had applications in skin rejuvenation, joint health, and tissue repair. Additionally, fish-derived enzymes, such as pepsin and trypsin, have shown promising applications in the food industry, biomedicine, and wastewater treatment due to their biodegradability and functional properties. These functional ingredients were widely utilized in dietary supplements, functional foods, pharmaceuticals, and cosmeceuticals. Advances in bioprocessing technologies enhance their extraction and bioavailability, further promoting their commercialization. The valorization of fishery by-products not only reduced environmental waste but also supported a circular economy. This review explored the key bioactive compounds derived from fishery by-products, their health benefits, and their growing applications in nutraceutical and pharmaceutical industries.